The Stringbags - Ennis, Garth (Dead Reckoning, 2020)
"Nazi Germany, Imperial Japan, and Fascist Italy began World War II with torpedo bombers that could devastate enemy warships and merchantmen at will. Britain's Royal Navy squadrons went to war equipped with the Fairey Swordfish. A biplane torpedo bomber in an age of monoplanes, the Swordfish was underpowered and under-gunned; an obsolete museum piece, an embarrassment. Its crews fully expected to be shot from the skies. Instead, they flew the ancient "Stringbag" into legend."--